Short-term high-fat diet increases macrophage markers in skeletal muscle accompanied by impaired insulin signalling in healthy male subjects - Boon, Mariëtte R.; Bakker, Leontine E. H.; Haks, Mariëlle C.; Quinten, Edwin; Schaart, Gert; Van Beek, Lianne; Wang, Yanan; Van Schinkel, Linda; Van Harmelen, Vanessa; Meinders, A. Edo; Ottenhoff, Tom H. M.; Van Dijk, Ko Willems; et al. (Clinical science (1979), 2015)
Macrophage markers in skeletal muscle of obese subjects are elevated and inversely relate to insulin sensitivity. The present study aimed to investigate whether short-term high-fat high-calorie (HFHC) diet already increases macrophage markers and affects glucose metabolism in skeletal muscle of healthy lean subjects. Muscle biopsies were obtained from 24 healthy lean young men before and after a 5-day HFHC-diet. mRNA expression levels of relevant genes in muscle and glucose, insulin, C-peptide and cholesteryl ester transfer protein (CETP) levels in plasma were measured. In addition, we assessed hepatic triacylglycerol (‘triglyceride’) (HTG) content by magnetic resonance spectroscopy and subcutaneous white adipose tissue (sWAT) biopsies were analysed histologically from a subset of subjects (n=8). A 5-day HFHC-diet markedly increased skeletal muscle mRNA expression of the general macrophage markers CD68 (3.7-fold, P<0.01) and CD14 (3.2-fold, P<0.01), as well as the M1 macrophage markers MARCO (11.2-fold, P<0.05), CD11c (1.8-fold, P<0.05) and MRC1 (1.7-fold, P<0.05). This was accompanied by down-regulation of SLC2A4 and GYS1 mRNA expression, and elevated plasma glucose (+4%, P<0.001) and insulin (+55%, P<0.001) levels together with homoeostasis model assessment of insulin resistance (HOMA-IR) (+48%, P<0.001), suggesting development of insulin resistance (IR). Furthermore, the HFHC-diet markedly increased HTG (+118%, P<0.001) and plasma CETP levels (+21%, P<0.001), a marker of liver macrophage content, whereas sWAT macrophage content remained unchanged. In conclusion, short-term HFHC-diet increases expression of macrophage markers in skeletal muscle of healthy men accompanied by reduced markers of insulin signalling and development of IR. Therefore, recruitment of macrophages into muscle may be an early event in development of IR in response to short-term HFHC-feeding.